Clinical study (phase II) of the efficacy and safety of Longidase (suppositories) in patients with adhesions due to pelvic inflammatory disease: A blinded, placebo-controlled, randomized study - Vera N. Prilepskaya; Elmira R. Dovletkhanova; Antonina V. Ledina; Aigun V. Tagieva (IP Berlin A.V., 2024)
Background. Pelvic inflammatory disease (PID) is a significant gynecological problem. The main treatment strategy involves antibacterial drugs to eliminate the infection in combination with anti-inflammatory, infusion, transfusion, anticoagulant, and desensitization therapy. Chronic inflammatory processes can induce changes in the immune system, thus reducing the effectiveness of treatment, causing adhesions, obstruction of the fallopian tubes, and infertility. It emphasizes the importance of developing new PID treatment methods, including using agents with immunomodulatory, antioxidant, and enzymatic activity that can increase the body's overall resistance to infections. Aim. To evaluate the effectiveness of Longidase® in treating pelvic adhesions to improve the outcomes in chronic PID. Materials and methods. The study included 50 women of reproductive age with established chronic PID and adhesions aged 18 to 42 years with a mean age of 29.4±5.8 years. The subjects were randomly assigned to two groups comparable in their main prognostic features. Patients of the main group (30 people) received treatment with Longidase® 3000 IU 1 suppository rectally once every 3 days, 10 doses, then 1 suppository once every 5 days, 5 doses (the total course is 15 doses of Longidase suppositories 3000 IU). Patients in the control group (20 people) received placebo. The treatment course was 55 days. The patients were followed up for up to 140 days from the start of therapy. Results. The results show no significant changes and the negative effect of the treatment on the blood chemistry parameters in both groups. In 35% of patients in the main group, the level of peptide-bound oxyproline did not change; 46% responded to therapy with its increase and 11% with a decrease, which indicates the activation of the decomposition of collagen proteins and a decrease in their synthesis. Analysis of individual levels of circulating immune complexes (CIC) before and after treatment showed a significant decrease in CIC in the main group (Longidase) vs. control group (36.1±1.4 and 30.8±0.8, respectively), which indicates a decrease in the severity of the inflammation. The pain relief, more pronounced during treatment in the main group than in the control group (30% vs. 15%), is probably due to the resolution of the chronic inflammation and correlates with changes in CIC. The onset of pregnancy in 10 (33.3%) patients in the main group indicates the effectiveness of bovhyaluronidase azoximer (Longidase®) as an anti-inflammatory and anti-fibrotic agent. Conclusion. The study showed the possibility of using Longidase 3000 IU suppositories in the complex therapy of patients with pelvic adhesions due to chronic PID